2009
DOI: 10.2987/08-5852.1
|View full text |Cite
|
Sign up to set email alerts
|

Larvicidal Activity and Influence of Bacillus thuringiensis Var. Israelensis on Aedes albopictus Oviposition in Ovitraps During A Two-Week Check Interval Protocol

Abstract: Toxicity persistence of Bacillus thuringiensis var. israelensis (Bti) was evaluated in laboratory and field trials to develop a new protocol for Aedes albopictus monitoring. In the laboratory, the residual toxicity of 5 Bti formulations was compared using the percentage mortality at days 4, 8, 12, and 16 of Culex pipiens larvae exposed for 24 h to Bti treatments. The results showed a good performance of all tested formulations (>97% mortality at day 14, for all the formulations), but only Vectobac 12AS at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
26
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 23 publications
4
26
1
1
Order By: Relevance
“…According to our Þndings, which are in agreement with Allan and Kline (1998) and Carrieri et al (2009), in Ae. albopictus the females per egg rate did not seem to be inßuenced by the egg density.…”
Section: Table 6 Number Of Containers With Water Positive Containersupporting
confidence: 92%
“…According to our Þndings, which are in agreement with Allan and Kline (1998) and Carrieri et al (2009), in Ae. albopictus the females per egg rate did not seem to be inßuenced by the egg density.…”
Section: Table 6 Number Of Containers With Water Positive Containersupporting
confidence: 92%
“…This reinforces the use of Bti as an efficient larvicide against urban mosquito species from the Culex and Aedes genera. In addition to the long persistence of Bti larvicidal activity in shaded areas , and the fact that no mosquito resistance has been recorded after decades of Bti use (Becker 1997, Regis et al 2001, this larvicide can help attract gravid females (Santos et al 2003, Stoops 2005, Carrieri et al 2009, Barbosa et al 2010, potentially promoting the concentration of mosquito eggs in lethal ovitraps. Due to the safety guaranteed by the persistent larvicidal action of Bti, frequent inspections of the traps, as performed throughout this study, is unnecessary.…”
Section: Discussionmentioning
confidence: 99%
“…israelensis (Bti) and Bacillus sphaericus may function as attractants for Aedes and Cux. quinquefasciatus mosquitoes (Poonam et al 2002, Santos et al 2003, Stoops 2005, Barbosa et al 2007, Carrieri et al 2009). …”
mentioning
confidence: 99%
“…Carrieri et al (2009) found that ovitraps containing 1% Bacillus thuringiensis var. israelensis (VectoBAC 12AS formulation) did not affect the oviposition response of gravid Aedes albopictus females and that it had a 100% lethal effect for at least 14 days, enough time to disrupt the reproductive cycle of Aedes.…”
Section: Discussionmentioning
confidence: 99%